hCG hormonal induction in wild queen drum Cynoscion albus in captivity - Boza Abarca, Jorge (2018)
The queen drum, Cynoscion albus is one of the 34 species distributed along the Central América pacific coast, which is captured with a trammel in the Gulf of Nicoya Because overfishing reports of sciaenid species in Costa Rica, the laboratory start a Sciaenid Reproduction Program to implement the reproduction in captivity The first specie was weakfish C squamipinnis which spawning in captivity after 2 5 years of adaptation without hormonal induction First generation also spawned applying the same protocols However, wild queen drums captured and transported to the laboratory at the same conditions of weakfish, not respond to the captivity reproduction strategies applied to weakfish, although both species share the same habitats and reproduction behavior The objective of this study was to evaluate the reproductive response of C albus to hCG hormonal induction in captivity.